1996
DOI: 10.1007/bf00144616
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of Fe(III), adriamycin and daunomycin with nucleotides and DNA and their effects on cell growth of fibroblasts (NIH-3T3)

Abstract: The interactions of the iron complexes of the anthracycline antitumour drugs daunomycin (DN) and adriamycin (ADM) with the mononucleotide AMP, herring sperm DNA, plasmic pBR322 and immortalized 3T3 fibroblasts were studied. By means of Mössbauer spectroscopy it was demonstrated that DNA is a powerful ferric iron chelator as compared with AMP, which is not able to compete with DN or acetohydroxamic acid for ferric iron. The difference between AMP and DNA is postulated to be based on the chelate effect. The Möss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…On the other hand, there was no correlation between copper and the number of AP sites. The above findings may be due to the nature of the DNA molecule as a powerful iron chelator [13]. In fact, iron has been documented as a key mediator of H 2 O 2 -induced DNA damage and development of hepatocellular carcinoma [35,15,28].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, there was no correlation between copper and the number of AP sites. The above findings may be due to the nature of the DNA molecule as a powerful iron chelator [13]. In fact, iron has been documented as a key mediator of H 2 O 2 -induced DNA damage and development of hepatocellular carcinoma [35,15,28].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that the cardiotoxicity of doxorubicin may be due to early damage to the DNA, mediated by hydroxyl free radicals of the alcohol metabolite. This damage to DNA may ultimately result in a decreased synthesis of proteins that are critical for the proper functioning of the myocardium (Crooke et al 1983 ;Mimnaugh et al 1983 ;Muindi et al 1984 ;Sinha et al 1984 ;Monti et al 1995 ;Di Liegro et al 1996). The reduction in the net intensity of the 110-kDa SR Ca 2 + protein band after repeated dosing with doxorubicin may be explained on the basis of the effect of free radical formation and doxorubicinol and the related decrease in protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11,14 Probably the other units present in anthracyclines assist hydroxy-9,10-anthraquinones in discharging its duties effectively. [19][20][21][22][23] The reason behind their formation is well known. This supports the general belief sugars play an important role in anticancer activity although a direct scientific justification is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] A study with carminic acid, having a sugar unit directly bound to a hydroxy-9,10-anthraquinone showed significant improvement in biophysical interactions and in experiments on cancer cells. [19][20][21][22][23] What is important is to show with suitably designed experiments that metal complexes (either of anthracyclines or of hydroxy-9,10-anthraquinones) are actually more effective cytotoxic agents than compounds from which they are prepared. Sugar(s), for example, is(are) believed to assist in drug binding to DNA and in recognition of cancer cells for which this moiety is often incorporated in a molecule during drug design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation